Inverse Opal Scaffolds with Gradations in Mineral Content for Spatial Control of Osteogenesis. Issue 29 (30th May 2018) - Zhu, Chunlei; Qiu, Jichuan; Pongkitwitoon, Suphannee; Thomopoulos, Stavros; Xia, Younan
Abstract: The design and fabrication of inverse opal scaffolds with gradations in mineral content to achieve spatial control of osteogenesis are described. The gradient in mineral content is established via the diffusion‐limited transport of hydroxyapatite nanoparticles in a closely packed lattice of gelatin microbeads. The mineral‐graded scaffold has an array of uniform pores and interconnected windows to facilitate efficient transport of nutrients and metabolic wastes, ensuring high cell viability. The graded distribution of mineral content can provide biochemical and mechanical cues for spatially regulating the osteogenic differentiation of adipose‐derived stromal cells. This new class of scaffolds holds promise for engineering the interfaces between mineralized and unmineralized tissues. Abstract : Inverse opal scaffolds with gradations in mineral content are fabricated by a simple and versatile method, for spatial control of osteogenesis. The graded scaffold can mimic the mineral distribution at the interface between connective tissues and bone, holding great potential for interfacial tissue engineering.